2008
DOI: 10.1186/ar2420
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cyclic citrullinated peptide antibodies in primary Sjogren's syndrome may be associated with non-erosive synovitis

Abstract: Introduction The purpose of this study was to investigate the prevalence of cyclic citrullinated peptide antibodies (anti-CCP) in patients with primary Sjögren syndrome (pSS) and its correlation with clinical and laboratory data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
41
3
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 23 publications
(24 reference statements)
11
41
3
2
Order By: Relevance
“…The most striking datum of Payet's study was represented by the very high prevalence of anti-CCP in CTD (17.5% vs 5.1% found in our series), with a peak in patients with SS (33%), strongly different from that found in our cohort (8.6%) and in 2 other previously published studies (7.5% and 9.9%) 9,10 . Notably, all anti-CCP-positive patients with SS described by Payet had joint involvement, with evidence of synovitis in the great majority (82%).…”
Section: Anticyclic Citrullinated Peptide Antibodies In Patients Withcontrasting
confidence: 97%
See 1 more Smart Citation
“…The most striking datum of Payet's study was represented by the very high prevalence of anti-CCP in CTD (17.5% vs 5.1% found in our series), with a peak in patients with SS (33%), strongly different from that found in our cohort (8.6%) and in 2 other previously published studies (7.5% and 9.9%) 9,10 . Notably, all anti-CCP-positive patients with SS described by Payet had joint involvement, with evidence of synovitis in the great majority (82%).…”
Section: Anticyclic Citrullinated Peptide Antibodies In Patients Withcontrasting
confidence: 97%
“…Notably, all anti-CCP-positive patients with SS described by Payet had joint involvement, with evidence of synovitis in the great majority (82%). This agrees with Atzeni's investigation 10 , which reported a close association between anti-CCP and synovitis in SS. Interestingly, in our cohort, all SS patients with circulating anti-CCP were diagnosed with SS associated with RA.…”
Section: Anticyclic Citrullinated Peptide Antibodies In Patients Withsupporting
confidence: 93%
“…To date there are several reports evaluating the meaning of anti-CCP antibodies in connective tissue diseases other than RA; in systemic sclerosis (SSc) 2 and systemic lupus erythematosus (SLE) 3 these antibodies are markers of erosive arthritis, as we suggest in antisynthetase syndrome. In contrast, in Sjögren's syndrome 4 this association is lacking, although anti-CCP seem to be closely associated with the occurrence of synovitis.…”
Section: To the Editormentioning
confidence: 77%
“…This group could be either classified as having RA with secondary SS, or as pSS with anti-CCP and non-erosive arthritis. Although one cannot rule out the possibility that pSS patients with anti-CCP antibodies may progress to RA, a common observation is that non-erosive arthritis prevails in anti-CCP antibody-positive SS patients [51,53,54], whereas in RA anti-CCP is a marker of persistent, erosive disease [56].…”
Section: Cryoglobulins: Immunoglobulins That Typify Sjögren Syndrome mentioning
confidence: 97%
“…[51,52]. On the contrary, an Italian study of 141 pSS patients found a positive association of anti-CCP antibodies with non-erosive synovitis in multivariate analysis [53]. In all three cohorts SS patients fulfilling the ACR classification criteria for RA had been excluded from the analysis.…”
Section: Cryoglobulins: Immunoglobulins That Typify Sjögren Syndrome mentioning
confidence: 98%